Cardinium infection alters cotton defense and detoxification metabolism of its whitefly host. (5th July 2022) - Liu, Ying; Yang, Kun; Wang, Jicheng; Chu, Dong
Abstract: Field monitoring revealed that the infection ratio of the bacterial symbiont Cardinium in the whitefly ( Bemisia tabaci MED) was relatively low in northern China. However, the role of this symbiont and the symbiont–whitefly–host plant interaction mechanism are poorly understood. We investigated the influence of Cardinium on the competitiveness of the host whitefly and the physiological interaction between the host plants and host whiteflies. Cardinium‐ infected whiteflies were displaced by uninfected whiteflies after 5 generations, which showed that Cardinium infection reduced whitefly competitiveness. The defense response genes of cotton significantly decreased under infestation by infected whiteflies compared to uninfected whiteflies. The expression of detoxification metabolism genes, especially the uridine 5ʹ‐diphospho‐glucuronyltransferase and P450 genes, in infected whiteflies significantly decreased. These results demonstrated that Cardinium could inhibit the defense response of the host plant and decrease the detoxification metabolism ability of the host whitefly. The reduced competitiveness of infected whiteflies may be associated with the inhibition of the whitefly detoxification metabolism by Cardinium, resulting in the reduced performance of infected whiteflies. However, Cardinium infection can suppress plant defenses, which may benefit both infected and uninfected whiteflies when they coexist. This research illustrates the symbiont–whitefly–host plant interaction mechanism and the population dynamics of the whitefly. Abstract : We investigated the influence of Cardinium on competitiveness of the host whitefly and the physiological interaction between plant and host whitefly. This research provides new data on the interaction mechanism between Cardinium and host whitefly and field population dynamics of the whitefly.